2021
DOI: 10.3346/jkms.2021.36.e176
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Radial Probe Endobronchial Ultrasound Guided Transbronchial Lung Biopsy in Bronchus Sign Negative Peripheral Pulmonary Lesions

Abstract: Background The presence of the bronchus sign on chest computed tomography is associated with an increased diagnostic yield of radial probe endobronchial ultrasound–guided transbronchial lung biopsy (RP-EBUS-TBLB). However, the utility of RP-EBUS-TBLB for bronchus sign negative peripheral pulmonary lesions (PPLs) remains unknown. We investigated the utility of RP-EBUS-TBLB in bronchus sign negative PPLs. Methods We retrospectively reviewed data from 109 patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…In CT-BS group II, a solid lesion was an independent factor affecting diagnostic success, in addition to rEBUS and fluoroscopic visualization as in group I. This was similar to that reported in a previous study [ 34 ]. CT-BS group II was classified into two or four types in the literature.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In CT-BS group II, a solid lesion was an independent factor affecting diagnostic success, in addition to rEBUS and fluoroscopic visualization as in group I. This was similar to that reported in a previous study [ 34 ]. CT-BS group II was classified into two or four types in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Despite minor differences in classification, Tsuboi type III, CT-BS 1 reported by Tokoro et al, type B reported by Minezawa et al, and CT signs type 2 reported by Shinagawa et al corresponded to bronchus type IIa in this study [ 10 , 18 , 19 , 20 , 21 ]. This type is typically classified as positive CT-BS [ 10 , 16 , 21 , 23 , 32 ], while studies focusing on negative CT-BS are considered negative [ 34 , 35 ], with a diagnostic yield ranging from 37.9% to 74.1%. Among CT-BS group II types, type IIa has a higher rEBUS visualization yield [ 20 , 34 ]; however, it contains many “adjacent to” images with comparable diagnostic performance relative to other types [ 36 ] or intermediate to CT-BS group I [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Precise positioning for sputum expectoration is a nursing operation that focuses on expectoration in the specific location and range of sputum accumulation area, atelectasis area, or lung lesions based on dynamic combination of lung ultrasound examination results, which can be targeted for sputum removal and more effectively remove sputum in the infected area, thus reducing the severity of PI. In addition, by reducing sputum accumulation, it can promote lung recruitment maneuvers and further improve PF [ 13 , 14 ]. In this study, the sputum volume was less, and the respiratory frequency and CPIS score were lower in the observation group versus the control group after 7 days of intervention, indicating that the application of precise positioning for sputum expectoration for the nursing of ICU patients with PI could reduce the sputum excretion and the severity of PI.…”
Section: Discussionmentioning
confidence: 99%